Analisis Framing pada Pemberitaan Kasus Penipuan Trading Online Indra Kenz di Kompas.com dan Detik.com - Ade Leasfita; Muhammad Budi Santoso (MUKASI: Jurnal Ilmu Komunikasi, 2023)
This research discusses two quite large media, namely Kompas.com and Detik.com, regarding the choice of point of view and framing of news regarding the suspect in the online trading fraud case committed by Indra Kenz. Researchers used two news samples each in the media Kompas.com and Detik.com which were presented on February 25 2022. This research discusses framing analysis, the aim of the research is to understand the framing in the reporting of the Indra Kenz online trading fraud case in Kompas. com and detik.com, using the framing analysis model from Pan & Kosicki. The research approach used is qualitative with Pan & Kosicki framing analysis, where the data used for this research is primary data with non-participant observation techniques obtained from the news portals Kompas.com and Detik.com. The research results obtained show that there are differences in the framing of news carried out by the online media Kompas.com and Detik.com. If you look at the news content on kompas.com and detik.com, they have their own ways of constructing news that is presented to the reading public.